Translating Pagu’s 'Industrial Park': São Paulo in 1933: Internationalizing the Modernist (Gragoatá, 2019)
Testimonial on the translation ofGALVÃO, P. Industrial Park. Elizabeth Jackson and K. David Jackson, trans. Lincoln: U Nebraska P, 1993.----------------------------------------------------------------------------------------------TRADUZINDO O PARQUE INDUSTRIAL DE PAGU: SÃO PAULO, 1933 - INTERNACIONALIZAÇÃO DO ROMANCE MODERNISTA.Depoimento sobre a tradução de:GALVÃO, P. Industrial Park. Elizabeth Jackson and K. David Jackson, trans. Lincoln: U Nebraska P, 1993.